PERAN CRIMINAL PROFILING TERHADAP PELAKU PEMBUNUHAN THE ROLES OF CRIMINAL PROFILING ON MURDERES - Arinda Nasywa Fadillah; Alya Shalsabilla Juliyanti, Putri Cinta Maulida Fahsa, Nisrina Sholihah, Rahma Meilina Arrazi, Stefa (CV. ADIBA AISHA AMIRA, 2025)
Criminal Profiling is an analysis method used in crime investigations to determine the characteristics of the perpetrators, by examining the evidence found at the crime scene. This study aims to assist investigators in compiling a physical, demographic and psychological picture of the perpetrator of the crime by analyzing the pattern of actions or characteristics seen in the crime. The method used in this study is systematic literature review. The criteria for the literature of this research are in the form of journals sourced from google scholar, garuda, and articles with full text. In this study, significant results were shown, especially murder by inferring the characteristics of the perpetrator in a descriptive way of criminal behavior. With criminal profiling, it is easier to investigate to find out the motive and perpetrator of the murder.